Heritability for Stroke: Essential for Taking Family History - Masoumeh Pourasgari; Ashraf Mohamadkhani (Babol University of Medical Sciences, 2020)
Background: There are many well-established factors that influence the risk of stroke including blood pressure, diabetes, low socioeconomic status and smoking, however, the shared genetic resource in members of a family effect on stroke predisposition. Genomewide association studies (GWAS) have demonstrated evidence of a shared genetic source in stroke risk. This review considered the influence of family history as one of the main risk factors in stroke according to the literature. Methods: Literature review was obtained by searching for the key words "stroke", "family history" and "stroke gene" in PubMed. An overview has been made on the topics: relevance of stroke family history, family history assessment tools and specific candidate genes for stroke. Results: Family history of stroke is an important risk factor for the development of cerebrovascular diseases in addition to stroke subtypes in relatives who have reached the questionnaire and pedigree. While variation in a small number of loci showed Mendelian inheritance of stroke phenotypes, the genetic variations in several stroke risk loci are shared with multiple related vascular traits. Conclusion: This study highlighted the importance of family history in stroke phenotypes and current related genetics information. Increasing awareness of the importance of family history in stroke has the advantage of preventing exposure to stroke with health care.